Penerapan Model Pembelajaran Gerak Dasar Atletik Nomor Tolak Peluru Berbasis Barcode pada Siswa Fase D Kelas V III SMPN 1 Indralaya Utara - Bagas Adi Nugroho; Hartati; Arizky Ramadhan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to describe the implementation of a barcode-based learning model for basic athletic movements in the shot put for Phase D grade VIII students at SMP Negeri 1 Indralaya Utara. The research method used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of the barcode-based learning model increased student motivation, facilitated understanding of basic shot put techniques, and increased student active engagement during the learning process. The barcode media, integrated with flashcards, enabled students to learn the material independently, repeatedly, and in a more focused manner through movement visualization. In conclusion, the barcode-based learning model is considered effective as an innovative learning medium for Physical Education (PJOK) in the shot put. Keywords: Athletics, Barcode, Learning Media, Physical Education (PJOK) Learning, Shot Put